Two types of two-component gels formed from pseudoenantiomeric ethynylhelicene oligomers - Yamamoto, Koji (Langmuir : the ACS journal of surfaces and colloids, 2012)
Two-component gels formed from pseudoenantiomeric ethynylhelicene oligomers in toluene exhibited two different properties depending on difference in numbers of helicenes in the two components. The combinations (M)-5/(P)-4, (M)-6/(P)-4, and (M)-7/(P)-4, which contained oligomers with comparable numbers of helicenes, formed transparent gels (Type I gels). The combinations (M)-6/(P)-3, (M)-7/(P)-3, and (M)-8/(P)-3, which contained oligomers with considerably different numbers of helicenes, formed turbid gels (Type II gels). Negative Cotton effects were observed for the Type I gels in the region between 350 and 450 nm, and were positive for the Type II gels, despite the use of (M)-oligomers for the longer components. UV/vis exhibited absorption maxima at 350 nm for the Type I gels and at 338 nm for the Type II gels. Different behaviors in gel formation processes were observed by fluorescence studies. Atomic force microscopy analysis showed fiber structures of 25-50 nm diameter for Type I gels and bundles of 100-150 nm diameter for Type II gels. The stoichiometry in gel formation also differed: The Type I gels showed 1:1 stoichiometry of the two components; the Type II gels showed no 1:1 stoichiometry, likely 1:2 stoichiometry. Using the Type I and II gels, two-layer gel systems were constructed